The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11270-009-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Dry Atmospheric Contribution to the Plant–Soil System Around a Cement Factory: Spatial Variations and Sources—a Case Study from Oman

Abstract: The present study determines the source of dust particles and investigates their impact on the chemical compositions of plants and soils around a cement factory in Oman within a radius of 10 km of this disturbed ecosystem. A total number of nine samples of the species of plants (Rhazya stricta), nine samples of soils, and nine samples of dust were collected and analyzed for major ions and trace elements including rare earth elements (REEs). Principal component analysis applied to the major and trace element co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Metal contamination of surface soils [1], agricultural soils [2,3], from industries [4][5][6] and waste disposal sites [7] are well known. Heavy metals in the soil can also generate airborne particles and dust, especially in dry seasons, which affects the air quality [8,9] Dust pollution has also been found to be problematic around cement factories [10,11]. In a study by Khashman and Shawabkeh 2006, soils around cement factories show high concentrations of heavy metals especially Pb, Zn and Cd on top soils of 0-10 cm deep.…”
Section: Introductionmentioning
confidence: 99%
“…Metal contamination of surface soils [1], agricultural soils [2,3], from industries [4][5][6] and waste disposal sites [7] are well known. Heavy metals in the soil can also generate airborne particles and dust, especially in dry seasons, which affects the air quality [8,9] Dust pollution has also been found to be problematic around cement factories [10,11]. In a study by Khashman and Shawabkeh 2006, soils around cement factories show high concentrations of heavy metals especially Pb, Zn and Cd on top soils of 0-10 cm deep.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Semhi et al on dust emitted from cement industries in Oman showed high concentrations of heavy metals in soils within a radius of 0.5-2 km around a cement factory [9]. A study on the effect of cement dust after 25 years of cement production on soil physicochemical properties by Asadu and Agada has revealed that exchangeable Ca, Na, H, and Mg, as well as soil organic matter, were significantly higher in the affected soils than in the non-affected soils [10].…”
mentioning
confidence: 99%
“…According to Semhi et al, high levels of heavy metals such as manganese might result from contributions from other sources such as agricultural run-off and local geological formations [50]. However, Iqbal et al [40] suggested that depending on the dust load, duration and tolerance of the plants, particulates might cause negative changes in the leaf surface ultrastructures, inhibit growth of the plants, reduce the area of leaves, and hence reduce total biomass.…”
Section: ) Concentration Of Heavy Metals In Cassava Leaves and Tubermentioning
confidence: 99%